Altered Cell Adhesion and Glycosylation Promote Cancer Immune Suppression and Metastasis - Läubli, Heinz; Borsig, Lubor (Frontiers in Immunology, 2019)
Cell-cell interactions and cell adhesion are key mediators of cancer progression and facilitate hallmarks of cancer including immune evasion and metastatic dissemination. Many cell adhesion molecules within the tumor microenvironment are changed and significant alterations of glycosylation are observed. These changes in cell adhesion molecules alter the ability of tumor cells to interact with other cells and extracellular matrix proteins. Three families of cell-cell interaction molecules selectins, Siglecs and integrins have been associated with cancer progression in many preclinical studies, yet inhibition of cell adhesion as therapeutic target is just beginning to be explored. We review how cell-cell interactions mediated by integrins and the glycan-binding receptors selectins and Siglec receptors are supporting cancer progression. The discussion is focused on mechanisms during immune evasion and metastasis that can be therapeutically targeted by blocking these cell-cell interactions.